Global burden of chronic kidney disease due to hypertension attributable to dietary risks in adults aged 25 years and older: findings from the global burden of disease study 2021 - Huang, Lianjie; Qiu, Yujie; Long, Zheng; Ding, Caicui; Gong, Weiyan; Liu, Ailing (Frontiers in Nutrition, 2025)
BackgroundSuboptimal diet remains a major threat to chronic kidney diseases (CKD) and hypertension, however, the burden of diet-attributable CKD due to hypertension (HCKD) has been poorly quantified and reported. This study aimed to provide a comprehensive and up-to-date view of global temporal and geographical trends in diet-attributable HCKD burden.MethodsData on diet-attributable HCKD burden were extracted from the Global Burden of Disease Study (GBD) 2021. Number and age-standardized rates (ASR) of mortality and disability-adjusted life years (DALYs) with their average annual percentage change (AAPC) were used to describe the diet-attributable HCKD burden. Decomposition analysis was employed to assess the contributions of aging, population, and epidemiological changes to HCKD burden.ResultsGlobally, the ASR of mortality (ASMR) and DALYs (ASDR) of diet-attributable HCKD among adults aged ≥25 years increased from 3.7 (95% uncertainty interval [UI]: 2.0–5.6) and 91.7 (50.1–140.1) per 100,000 population in 1990 to 4.3 (2.3–6.7) and 101.2 (56.0–154.5) per 100,000 population in 2021, respectively. Both mortality and DALYs of diet-attributable HCKD burden in 2021 were higher among males than females. Low fruit and low vegetable intake contributed the most to the diet-attributable HCKD burden. The highest ASMR and ASDR of diet-attributable HCKD were observed in Central Sub-Saharan Africa, whereas the lowest were observed in Eastern Europe. The older adult population had higher mortality and DALYs than other age groups. Decomposition analysis showed that population growth mainly contributed to HCKD burden, particularly in low SDI regions.ConclusionThe diet-attributable HCKD burden is increasing at an alarming rate globally, especially in low SDI countries and older adults. This study emphasizes the urgent need for rigorous public health interventions to change unhealthy dietary behaviors and decrease diet-attributable HCKD burden worldwide.